Fast-Velocity Eccentric Cycling Exercise Causes Greater Muscle Damage Than Slow Eccentric Cycling - Ueda, Hisashi; Tsuchiya, Yosuke; Ochi, Eisuke (Frontiers in Physiology, 2020)
This study aims to investigate muscle damage occurring in the early and recovery phases after fast-velocity and slow-velocity eccentric cycling. Eleven untrained men (age, 20.0 ± 1.7 years; height, 171.3 ± 6.8 cm; weight, 61.8 ± 7.7 kg; %body fat, 13.2 ± 2.9%) performed slow-velocity maximal isokinetic eccentric cycling (slow-velocity; 30°/s) with one leg and fast-velocity (fast-velocity; 210°/s) isokinetic eccentric cycling with the other leg. Changes in maximal voluntary concentric contraction (MVCC) torque at velocities of 30°/s and 210°/s, range of motion (ROM), muscle soreness based on a visual analog scale, thigh circumference, muscle echo intensity, and muscle stiffness were assessed before exercise, and immediately, 1, and 4 days after exercise. Comparing with the results obtained for slow-velocity cycling and before exercise, MVCC during fast-velocity cycling significantly decreased at immediately, 1, and 4 days after exercise (p < 0.05). Significant increase in muscle soreness for vastus lateralis was observed during fast-velocity cycling compared with slow-velocity cycling 4 days after exercise (p < 0.05). However, no significant difference in muscle soreness was observed for rectus femoris and vastus medialis at any time points after exercise. In addition, no significant differences were observed in the ROM, thigh circumference, muscle echo intensity, and muscle stiffness. We conclude that fast-velocity eccentric cycling causes greater muscle damage than slow-velocity eccentric cycling.